Traces of a Swedish army camp from 1644 revealed at Uppåkra by extensive magnetometer survey. Issue 1 (28th July 2021) - Trinks, Immo; Gabler, Manuel; Wallner, Mario; Nau, Erich; Hinterleitner, Alois; Filzwieser, Roland; Larsson, Lars; Neubauer, Wolfgang
Abstract: In the framework of an archaeological prospection case study conducted at the Swedish Iron Age site of Uppåkra near Lund, a large number of anomalies caused by buried archaeological remains were detected using extensive magnetic surveys. Written sources report that the Swedish army under Field marshal Gustav Horn had established a camp near the village of Uppåkra in autumn 1644, awaiting the approaching Danish army. Magnetic anomalies of two large, square structures, numerous pits and several pit alignments have been interpreted as possible traces of buried remains of this army camp. We present archaeological prospection data from Uppåkra with regard to the events that took place during Horn's war in 1644.